Efficiency and Sustainability in Biofuel Production 2015
DOI: 10.1201/b18466-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Marginal Land Resources Suitable for Developing Bioenergy in Asia

Abstract: The need for sustainable biofuels has initiated a global search for innovative technologies that can sustainably convert nonfood bioresources to liquid transportation fuels. While 2nd generation cellulosic ethanol has begun to address this challenge, other resources including yellow and brown grease are rapidly evolving commercial opportunities that are addressing regional biodiesel needs. This review examines the technical and environmental factors driving the collection of trap FOG (Fats, Oils, and Greases),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The sulfur content of BGL is highly variable and typically is between 200 and 400 ppm, although we have obtained BGL samples with higher than 500 ppm and as low as 100 ppm (Cairncross et al, ). In agreement with the observations made by He et al (), several researchers have reported that the sulfur content in FAME is less than the sulfur content in the parent oil (Alleman et al, ; Kim et al, ; Ma et al, ; Ragauskas et al, ). BGL typically contains 230–850 ppm S and in most cases, is reduced nearly into half upon transesterification to FAME (Cairncross et al, ; Chakrabarti et al, ; Gardner et al, ; Hums et al, ).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The sulfur content of BGL is highly variable and typically is between 200 and 400 ppm, although we have obtained BGL samples with higher than 500 ppm and as low as 100 ppm (Cairncross et al, ). In agreement with the observations made by He et al (), several researchers have reported that the sulfur content in FAME is less than the sulfur content in the parent oil (Alleman et al, ; Kim et al, ; Ma et al, ; Ragauskas et al, ). BGL typically contains 230–850 ppm S and in most cases, is reduced nearly into half upon transesterification to FAME (Cairncross et al, ; Chakrabarti et al, ; Gardner et al, ; Hums et al, ).…”
Section: Introductionsupporting
confidence: 86%
“…Desulfurization of fatty acid methyl esters (FAME, the principal component of biodiesel) produced from brown grease lipids (BGL) has been identified by the industry as a major hurdle to utilizing brown grease as a biodiesel feedstock (Ragauskas, Pu, & Ragauskas, ). BGL refers to the lipid components of wastewater residuals, such as GTW and SSG that are insoluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…Abdulla and Ravindra [36] immobilized lipase from Burkholderia cepacia to catalyze the transesterification of crude J.curcas L. oil to achieve 73% methyl ester conversion and the immobilized lipase remained stable after six successive cycles of reuse. Ragauskas et al [37] made use of Rhizopus oryzae as biocatalyst in the conversion of three different oils under the favourable reaction conditions. However, as widely reported in the literature, enzymatic transesterification reaction needs to be carried out at moderate condition so as to prevent enzyme deactivation [38], besides, enzyme-catalyzed transesterification is not cost effective, because enzymes are costly and require a prolong period of reaction [34].…”
Section: Catalysts In Transesterification Reactionmentioning
confidence: 99%
“…Lately, interests have grown in utilizing sewer/trap grease for biodiesel production (Ragauskas et al, 2013;López et al, 2014) to reduce feedstock cost. Biodiesel feedstock cost can take up to 80% of the total production cost (Haas and Foglia, 2005), which motivated research and development for low cost alternatives, especially from non-food sources.…”
Section: Introductionmentioning
confidence: 99%